Assessing the impact of verbal and written oral hygiene instructions on orthodontic patient outcomes - Umer Farooq; Mariyah Javed; Zartashia Arooj; Kashif Haroon; Mamoona Luqman; Sadia Manzoor (Journal of University Medical & Dental College, 2024)
ABSTRACT BACKGROUND & OBJECTIVE: Due to increasing trends in orthodontic treatment to improve occlusal relationships and smile esthetic, maintenance of oral hygiene should be the first priority of the patient. Different methods were used for oral hygiene instructions (OHI) which included chair-side education, message reminders, and behavioral modification. The objective of this study was to compare the oral hygiene status of patients given verbal instructions and written instructions. METHODOLOGY: The comparative study includes 50 orthodontic patients selected from the age group 12-30 years from the orthodontic department of Azra Naheed Dental College Lahore. They divided into two groups: group one was given verbal instructions and group two was given written. Plaque disclosing agent was applied to the upper anterior teeth and the color displayed in response was recorded. After a month the status and results of oral hygiene were again evaluated for both groups. RESULTS: The results showed that the patients who were given written oral hygiene instructions showed better maintenance of oral hygiene with p-value ≤ 0.001 showing significant results when compared with those who were given verbal instructions with p-value = 1.00 showing non-significant results. Plaque index as disclosing agents didn’t show any blue pigmentation in written OHI, while blue pigmentation was observed in verbal OHI. CONCLUSION: The patients given written oral hygiene instructions responded better as compared to the patients given verbal instructions which also enhanced patient cooperation.